flexZhouse: new business model for affordable housing in Malaysia - Mohd Noor, Mohd Zairul (TU Delft, 2017)
Central to this PhD research is the problem of the lack of affordable housing for young starters in Malaysia. The solutions for affordable housing that are available in the market do not truly solve the problem from the customer’s point of view. Hence, it was important to analyse the contributing factors associated with the term ‘affordability’. Affordability touches upon interconnected elements that cover many issues ranging from demand (housing needs, demographics, household income, quality housing) to supply (the authorities’ requirements, design, cost, sustainability and procurement). In this thesis, we discuss some of the problems related to the supply and demand issues and examine a possible intervention to solve the problem. This research contributed to the body of knowledge by employing a prescriptive strategy and designing an innovative flexZhouse business model (BM), and by applying an in-depth strategy that revealed why the problem exists and why there is still no appropriate solution. The result provides a description of the situation that young starters find themselves in, the reactions of the industry’s key players and the policies that hamper innovation in the housing market. The flexZhouse BM combines innovative leasing with elements of the circular economy as part of the strategy to provide affordable housing to the customer. The research contributes to the scientific community by combining the idea of industrialized housing production with innovative leasing inspired by circular economy principles. This thesis is the first study to suggest integrating flexible housing with the circular economy. It therefore fills a gap in the knowledge about industrialized housing and industrialized building (IB) industry. The research, which pursued the identified problems by developing a new BM, will benefit the government of Malaysia, as it formulated a solution for affordable housing schemes and created an alternative BM for the housing industry.